2022
DOI: 10.3389/fmed.2022.826705
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Early Distant Metastatic Inflammatory Myofibroblastic Tumor Harboring EML4-ALK Fusion Gene: Study of Two Typical Cases and Review of Literature

Abstract: Inflammatory myofibroblastic tumor (IMT) is a distinctive neoplasm that frequently arises in the lung and accounts for ~1% of lung tumors. Distant metastatic IMT is extremely rare and has been poorly investigated. This analysis was specifically performed to explore the clinicopathological and genetic features of early distant metastatic IMT. Two typical patients with distant metastatic IMTs were selected, which accounted for 1.13% of all diagnosed IMTs in the last 5 years. One patient was a 55 year-old male, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…Qianqian et al reported the rate to be 1.13% at their own institution. 4 The most commonly reported metastatic organs of IMT are lung, brain, and bone; brain metastases were found in six of 50 metastatic IMT cases. 4 Previous reports have shown that 50% of surgically resected IMT cases are positive for ALK rearrangement.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Qianqian et al reported the rate to be 1.13% at their own institution. 4 The most commonly reported metastatic organs of IMT are lung, brain, and bone; brain metastases were found in six of 50 metastatic IMT cases. 4 Previous reports have shown that 50% of surgically resected IMT cases are positive for ALK rearrangement.…”
Section: Discussionmentioning
confidence: 97%
“…4 The most commonly reported metastatic organs of IMT are lung, brain, and bone; brain metastases were found in six of 50 metastatic IMT cases. 4 Previous reports have shown that 50% of surgically resected IMT cases are positive for ALK rearrangement. 5 Considering the fact that 19 of 37 patients with metastatic IMT were ALK-positive, 4 there seems no difference in the frequency of ALK rearrangement positivity between metastatic and nonmetastatic IMT.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These morphological features are reminiscent of the spindle cell variant of epithelioid cell histiocytofibroma [ 7 ], which has been reported to present ALK fusions with DCTN1 , TMP3 and EML4 genes [ 8 ]. Furthermore, these fusions have also been identified in IMT [ 9 , 10 , 11 ]. IMT and EFH can both show cytoplasmic expression of ALK and factor XIIIa, but, unlike IMT and some classical benign fibrous histiocytomas, EFH does not express smooth muscle actin [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the World Health Organization states its nature as an intermediate malignant neoplasm with mesenchymal origin ( 2 ). IMT has been reported in almost all body and soft tissue visceral organs ( 3 , 4 ). Most recorded cases were in the lung, followed by the mesentery and the omentum ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%